2022
DOI: 10.1038/s41598-022-10361-2
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based online intervention increases well-being and decreases stress after Covid-19 lockdown

Abstract: Mindfulness interventions were shown to be effective in improving well-being and reducing perceived stress in several conditions. These effects were also found in online mindfulness-based training, especially in employees in organizational environments. The aim of this study was to test the effectiveness of an online mindfulness intervention on healthy employees, especially after the first Italian Covid-19 lockdown. Participants in the intervention group underwent an 8-week mindfulness online training program … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…Such findings are consistent with Ye and Lyu's ( 74 ) research, which suggests that risk perception is low for individuals with a high trust in government. Meanwhile, our findings also confirm Bossi et al's ( 23 ) and Matiz et al's ( 22 ) findings, who found that mindfulness-based training is beneficial for mitigating the negative impacts of the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such findings are consistent with Ye and Lyu's ( 74 ) research, which suggests that risk perception is low for individuals with a high trust in government. Meanwhile, our findings also confirm Bossi et al's ( 23 ) and Matiz et al's ( 22 ) findings, who found that mindfulness-based training is beneficial for mitigating the negative impacts of the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, individuals with a higher level of mindfulness often purposely focus their attention on their ongoing and present experiences, as well as maintain a non-judgmental attitude ( 19 , 21 ). Existing works suggest that mindfulness intervention is helpful for decreasing anxiety, depression, and emotional exhaustion during the COVID-19 pandemic ( 22 ), and is effective for relieving stress after COVID-19 lockdowns ( 23 ). Moreover, Zheng et al ( 24 ) indicated that the interaction between COVID-19 stressors and mindfulness could affect sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“…A study on operating room staff found that providing them with 30-min of music therapy three times a day for a consecutive month significantly decreased their emotional exhaustion, representing improved job burnout ( 51 ). In another pilot study, researchers chose mindfulness therapy based on an online app, which has also been shown to help reduce the stress and negative emotions of medical and non-medical participants, thereby improving burnout ( 52 , 53 ). We therefore recommend the use of non-drug interventions such as online mindfulness therapy or music therapy to help medical staff with job burnout during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention was effective in facilitating mindfulness practice, [179][180][181][182] as well as reducing stress, 178 and increasing well-being. 183 However, there are limitations to the research available, as the above findings are restricted to positive responses on self-report questionnaires of perceived well-being in relatively healthy samples.…”
Section: Situ Versus Emobile Interventionsmentioning
confidence: 98%